2000
DOI: 10.1021/ie000707u
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical Desulfurization and Denitrogenation Process for Vacuum Gas Oil Using an Organic Two-Phase Extraction System

Abstract: The simultaneous removal of sulfur-and nitrogen-containing compounds from vacuum gas oil (VGO), based on the combination of UV irradiation and liquid-liquid extraction using an oil/ acetonitrile two-phase system, has been investigated. Detailed desulfurization and denitrogenation reactivities for the various compounds in VGO have also been studied by means of field ionization mass spectrometry (FI-MS) and gas chromatography with atomic emission detection (GC-AED), respectively. When VGO and acetonitrile are mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
81
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(88 citation statements)
references
References 19 publications
3
81
2
Order By: Relevance
“…In addition, HDS generally requires high temperature (>300 C), high pressure (>4 MPa), consumption of H 2 and catalyst, etc (5,6). Therefore, various alternative or complementary desulfurization processes have been investigated to remove the HDS-immune S-compounds, for example, extractive (7)(8)(9)(10)(11)(12)(13)(14)(15)(16), oxidative (17)(18)(19), adsorptive, (20,21) and biodesulfurizations (22,23). Among them, extractive desulfurization seems more eye-catching because it does not require hydrogen and catalyst and its operation condition is mild; moreover, it does not alter the chemical structure of the compounds in fuel oils and the extracted S-compounds can be re-used as raw materials.…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
See 1 more Smart Citation
“…In addition, HDS generally requires high temperature (>300 C), high pressure (>4 MPa), consumption of H 2 and catalyst, etc (5,6). Therefore, various alternative or complementary desulfurization processes have been investigated to remove the HDS-immune S-compounds, for example, extractive (7)(8)(9)(10)(11)(12)(13)(14)(15)(16), oxidative (17)(18)(19), adsorptive, (20,21) and biodesulfurizations (22,23). Among them, extractive desulfurization seems more eye-catching because it does not require hydrogen and catalyst and its operation condition is mild; moreover, it does not alter the chemical structure of the compounds in fuel oils and the extracted S-compounds can be re-used as raw materials.…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
“…Very different from traditional molecular-type organic solvents, ILs are entirely composed of cations and anions, and possess some novel and desirable properties such as non-volatility, excellent selective solvent power for organic=inorganic compounds, good thermal=chemical stability, nonflammablity, etc (27,28). It is observed that ILs are almost insoluble in fuel oil and favorably disposed towards the extraction of thiophenic S-compounds, such as TS and DBT, over other aliphatic or aromatic compounds (11,12,29). Many ILs used in extractive desulfurization are mostly imidazolium-and pyridinium-based, coupled with anions such as tetrafluoroborate= [BF 4 ], hexafluorophosphate=[PF 6 ], chloride-based [Cl=AlCl 3 ], and [Cl=FeCl 3 ], bis(trifluoromethylsulfonyl)imide=[Tf 2 N], alkylsulfate, and alkylphosphate (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18).…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
“…Their works include the study on product identification and the effect of photosensitizer benzophenone on sulfur removal. [12][13][14][15][16] To improve sulfur removal, researchers also used TiO 2 as photocatalyst [17][18][19][20][21][22] because of its nontoxicity, chemical and photochemical stability, low cost, and excellent photocatalytic activity. 23,24 Above mentioned studies were all performed by UV light irradiation because the sulfur-containing compounds cannot be photodegraded itself under visible light.…”
Section: Introductionmentioning
confidence: 99%
“…The application of this photochemical oxidation to desulfurization as been realized in some literatures [22,23] using oil-water and oil-polar solvent two phase systems. The desulfurization of light oil to a sulfur content of less than 0.05 wt% has been achieved successfully.…”
Section: Introductionmentioning
confidence: 99%